Pengembangan E-Modul Dilengkapi Quick Respon (QR) Code Pada Materi Mobilitas Pada Manusia Fase F SMA/MA - Ardila, Dwisindi; Susanti, Diana; Afza, Aulia (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research aims to develop a biology e-module equipped with a Quick Response (QR) Code on the topic of human mobility, which is valid and practical for use by Phase F students at high school (SMA/MA) level. This research employs a development research method (R&D) using the 4-D model, which consists of the stages of Define, Design, Develop, and Disseminate. Due to time and budget constraints, this research was only conducted up to the development stage. Data were obtained directly from three lecturers and two teachers as validators. The validation aspects evaluated include content feasibility, language, presentation, and graphic design. Additionally, data from the practicality test questionnaires, administered to two teachers and 35 students, assessed ease of use, time efficiency in learning, and overall benefit. The data were processed using percentage formulas and analyzed descriptively with a Likert scale. The results of the study show that the e-module achieved a validity score in the "highly valid" category, with an average score of 95%. Moreover, practicality testing involving teachers and students indicated "highly practical" results, with an average of 95.54% for teachers and 91.42% for students. Based on these findings, it can be concluded that the e-module on the topic of human mobility for Phase F high school students is both highly valid and highly practical.